Lords of Misrule - Taylor, A. author. aut Link
XII, 233 p.
Keywords: Flamboyant, cultured and refined, aristocracy is often seen as a national treasure. Lords of Misrule takes a different view and considers the role of an aristocracy behaving badly. This is a book about the political, social and moral failings of aristocracy and the ways in which they have featured in political rhetoric. Drawing on the views of critics of aristocracy, it explores the dark side of power without responsibility. Less 'patrician paragons' than dissolute and debauched debtors, the aristocrats featured here undermined, rather than augmented, the fabric of national life. For the first time, Lords of Misrule recaptures the views of those radicals and reformers who were prepared to contemplate a Britain without aristocrats.